Assessing the Student Nurses' Knowledge of Oral Health Care - Gemma Marquès-Pellejà; Marta Roqueta-; David Cámara-Liebana; Susana Mantas-Jiménez; Sandra Gelabert-Vilella; Alícia Baltasar-Bagué; Glòria Reig-Garcia (MDPI AG, 2023)
Oral health is crucial for the overall well-being and quality of life, and nurses play a significant role in promoting it. This study assessed the oral health knowledge of fourth-grade nursing degree students. Seventy-two students completed a questionnaire covering sociodemographic variables, oral health-related factors, knowledge about oral health, and perceptions of its importance and learning experiences. The results showed that 83.3% of students attended regular dental check-ups for preventive purposes, and 55.6% had visited a dentist during the last year. Most of the students reported experiencing cavities (66.7%) and undergoing orthodontic treatment (54.2%). The average knowledge score in oral health was 6.4 out of 10, and students recognized the importance of oral health in the nursing role. However, their knowledge acquired during their nursing degree scored relatively low, being 2.5 out of 5. Notably, students who valued problem-based learning achieved higher knowledge scores (p < 0.05). Overall, fourth-grade nursing students demonstrated a moderate level of oral health knowledge. Improving oral health education within nursing curricula, particularly through problem-based learning, is essential to enhance their preparedness in addressing oral health issues effectively. This study was not registered.